STUDI PENERAPAN PSAK 45 YAYASAN PANTI ASUHAN YABAPPENATIM JEMBER - Norita Citra Yuliarti (Universitas Jember, 2014)
Yayasan Panti Asuhan Yabbapenatim in managing funds from donors, and distribution process more inclined to charity to help education, health assistance, and support working capital. In the case of this disclosure orphanage foundation has not made a note to the financial statements and for the presentation of its financial statements Yayasan Panti Asuhan Yabbapenatim make two simple financial statement balance sheet and statement of sources and utilization of funds. Yayasan Panti Asuhan Yabbapenatim has met the statutory regulations charity to make the financial statements. However, the components of financial statements that are made not complete and not fulfill the components of financial statements in accordance with IAS 45, because of limited funds and human resources are managed. The financial statements have not been audited by an independent auditor or by a public accounting firm. Because if the audited it will provide added value for Transparency and accountability to the financial statements he made that will increase public confidence in the Yayasan Panti Asuhan Yabbapenatim to manage,distribute and use it. Key words: Accounting Foundation, IAS 45, Financial Reporting.